Analisis Faktor Kepemimpinan, Pengetahuan, dan Sikap terhadap Perilaku Tidak Aman pada Pekerja Produksi Sauna di PT. XYZ - Nathasya Abigail Putri Andira; Fierdania Yusvita; Eka Cempaka Putri; Ahmad Irfandi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Unsafe behavior is behavior that deviates from generally recognized safe action or certain methods when someone do their task. Data from The Employment Insurance Agency (BPJS) in 2014 recorded 32,21% of accidents caused by unsafe behavior. Risk factors for unsafe behavior can be reviewed through personal factors such as knowledge and attitudes, as well as job factors such as leadership. This study aims to determine the description and relationship among leadership, knowledge, and attitudes with unsafe behavior of sauna production workers in PT XYZ in 2024. This type of research is quantitative with a cross-sectional study design conducted from March to August 2024. Data collection techniques using total sampling. Data collection using primary data through distributing questionnaires with samples of 65 respondents. Data were analyzed using univariate analysis and bivariate analysis with the chi-square test. Univariate results showed that the highest proportion of workers with unsafe behavior was 36 (55.4%), workers who assessed poor leadership were 47 (72.3%), workers with poor knowledge were 39 (60%), and workers with negative attitudes were 40 (61.5%). There is a relationship between leadership (P-value = .000), knowledge (P-value = .000), and attitude (P-value = .001) with unsafe behavior. For PT XYZ, it should be able to build a HSE department unit by strengthening management commitment with the involvement of leaders first in order to create programs that can improve workers knowledge and attitudes.